THE LEGAL NATURE OF THE REMUNERATION TO THE GUARDIAN OF THE ADULT INCAPACITATED CITIZENS - M. Sedelnikova; A. Puzyreva (Правоприменение)
УДК 347.163The main purposes of present article are the research of regulatory framework of establishment of repayment for tutors of emancipated incapable persons and legal practice of set-tlement of disputes in abovementioned sphere. Accumulation of methods of scientific cog-nition is a methodological outline of present research, the main methods are system-defined, technic and comparative ones.Based on deep analysis of federal and regional provisions of legislation maintained terms and conditions of payments of repayment for tutors of emancipated incapable persons the social and interim nature of aforementioned payments is concluded. Current state law actually allows to conclude that the state care for the socially vulnerable categories of the citizens, including the elderly and disabled citizens, with limited material resources, encourages the legislator to seek new alternative ways of its implementation. To those should be referred "social outsourcing", that is, privatization of "unprofitable" social services in order to optimize the budgetary resources. Meanwhile, the reduction of costs for the implemen-tation of the social functions of the state should not take place to the detriment of the content component.In the scientific literature there is no unanimity of views on the legal nature of the payments made by the trustees for the performance of such duties. Comparison of remuneration of trustees with a monthly payment for child care until the age of 1.5 years to achieve it possible to identify common objectives of establishing these payments, as well as the identity of their social and interim nature. Confirmation designated theses is to analyze the provisions of the legislation of the Russian Federation, in which the caregiver award is regarded as one of the ways to sequence the elimination of in-patient care and social services at home, which also contribute to the strengthening of social protection of this category of citizens.However, the practice of implementation of the provisions in the legislation found a num-ber of fundamental problems. In particular, the regulation of these relations norms different industry sector is the cause of the ambiguity of their interpretation. Judicial authorities misinterpreted the purpose of the above payments, ignoring their legal entity. The current judicial practice does not allow to achieve the objectives the legislator and has a negative impact on the social security of citizens.